2012
DOI: 10.1007/s00192-012-1829-5
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and urinary incontinence in US women

Abstract: Introduction and Hypothesis The goal of this study was to characterize associations between caffeine consumption and severity of urinary incontinence (UI) in US women. We hypothesized that moderate and high caffeine intake would be associated with UI in US women when controlling for other factors associated with UI. Methods US women participated in the 2005–2006 and 2007–2008 National Health and Nutrition Examination Survey (NHANES), a cross-sectional, nationally representative survey. Using the Incontinence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 25 publications
3
29
1
3
Order By: Relevance
“…Injury to pelvic floor muscles occurring during vaginal delivery may weaken the muscles leading to SUI in later life and provides a plausible explanation for the higher prevalence of UI with pregnancy and parity. Although abdominal surgery (other than LSCS), bronchial asthma and regular consumption of coffee did not seem to increase the prevalence of SUI in our study, these have been identified as risk factors in previous studies from the Northern Europe, Canada and United States [19,22,23]. Similar to the findings in the Canadian study [22] presence of chronic cough significantly increased the risk of SUI.…”
Section: Discussionsupporting
confidence: 82%
“…Injury to pelvic floor muscles occurring during vaginal delivery may weaken the muscles leading to SUI in later life and provides a plausible explanation for the higher prevalence of UI with pregnancy and parity. Although abdominal surgery (other than LSCS), bronchial asthma and regular consumption of coffee did not seem to increase the prevalence of SUI in our study, these have been identified as risk factors in previous studies from the Northern Europe, Canada and United States [19,22,23]. Similar to the findings in the Canadian study [22] presence of chronic cough significantly increased the risk of SUI.…”
Section: Discussionsupporting
confidence: 82%
“…A recent study also found that high caffeine intake (>450 mg/day) was associated with frequent UI and UUI [27]. Similar findings were also made by Gleason et al who reported that caffeine intake was associated with UI as well as with the degree of severity of UI [28]. The reason/s for this discrepancy in the association between UI and coffee consumption is unclear.…”
Section: Discussionsupporting
confidence: 59%
“…Race and ethnicity have been known to make a difference in the presence of UI due to variability in body mass index, the prevalence of UI-associated diseases such as diabetes, or dietary habits, including caffeine consumption, all of which differ by nation or region [ 1 4 ]. Caffeine is the most frequently consumed stimulant in the world, and over 80% of total caffeine consumption comes from coffee and other caffeine-containing beverages [ 11 ]. It has been thought that caffeine acts as a bladder-function stimulant through diuretic effects and other various mechanisms [ 8 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between caffeine consumption and UI remains controversial because of mixed research results. Some studies have reported that caffeine intake raises the incidence of UI, whereas others have found no association between caffeine intake and UI incidence in females [ 11 14 ]. Although caffeine intake is on the rise in Korea with the increasing consumption of coffee and soft drinks among Korean people due to the influence of Western diets and modes of life, one characteristic of a traditional Korean lifestyle is the low consumption of caffeine.…”
Section: Introductionmentioning
confidence: 99%